Dismantling Paradigm Book Talimul Mutaallim - Umah, Yuli Choirul (EDUCATIO : Journal of Education, 2016)
The wrong factor and careless of knowledge qualifications is mistake position in learning. Classification of knowledge such as knowledge must be learned and knowledge is forbidden to learn. The knowledge is forbidden to learn Becomes individual obligation as like Oneness of God, knowledge rep obligation as like legacy knowledge. One of an example of knowledge must be learned individually is attitude knowledge, modesty, and some other thing.